Impact of Physiotherapy with Unstable Platforms for the Prevention of Ankle Injuries and Improving Balance in Male Volleyball Players - Patrikas Stankevičius; Saulė Sipavičienė (Lithuanian Sports University, 2022)
Background. Ankle sprain is the most common sports injury. Conducting physiotherapy with unstable platforms efficiently decreases risk of ankle injuries and increases static and dynamic balance parameters. Aim. To estimate the effect of physiotherapy on balance of volleyball players and the prevention of ankle injuries. Methods. The study involved 10 male volleyball players, who were randomly divided into two groups: intervention (physiotherapy with unstable platforms) and control (no physiotherapy applied). Flamingo test and modified star excursion balance test were used before and after intervention. Duration of intervention - 4 weeks. Results. After 4 weeks of physiotherapy with unstable platforms static balance increased in intervention group subjects by 66.7% (p < 0,05); however, there were no changes in the control group. Post intervention examination showed statistically significant increase in Y balance test results in different directions, while the control group did not show any change. Conclusion. After a physiotherapy program with unstable platforms, static balance as well as dynamic balance increased. A 4-week physiotherapy program with unstable platforms significantly decreased the risk of ankle injuries in male volleyball players. Keywords: balance, ankle injury prevention, volleyball.